Implementation of Merdeka Curriculum in the Form of Culinary Training for Teachers and Students at UPT. SKB 1 Tanah Datar - Najmi, Najmi; Anggraini, Ezi; Salam, Abdul; Fitriah, Rahmuliani; Nasution, Annisa Annida; Abianza, Erza (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Sanggar Kegiatan Belajar (SKB) 1 Tanah Datar, located in Nagari Pagaruyung, Tanjung Emas District, Tanah Datar Regency, is a strategic educational institution with great development potential. Despite having adequate facilities and the support of committed educators, SKB 1 Tanah Datar faces obstacles in curriculum implementation, especially in the Pancasila Student Profile program. The implementation of this community service program aims to improve the competence of students and tutors at SKB 1 Tanah Datar, with a focus on culinary training. The implementation method includes coordination with the UPT SKB 1 Tanah Datar, theory and practice-based training, and evaluation to ensure the quality of training. Through the transfer of knowledge, sustainability, and income generation approaches. This training is expected to improve learners' skills, strengthen teachers' competencies, and create new business opportunities that support the economic welfare of especially learners (package B and C). The evaluation showed that despite challenges in teacher competence and curriculum understanding, this activity had a positive impact on developing the skills of learners and student teachers at SKB 1 Tanah Datar